A new entomopathogenic nematode species and its association with a facultative necromenic nematode - Ávila-López M. B.; Hernandez-Mena D. I.; Ibarra J. E.; Vidal-Martínez V. M. (Helminthologia, 2024)
This is the report of mixed infection of an entomopathogenic nematode and a free-living bacteriophage nematode both invading Galleria mellonella larvae, apparently showing strong intraguild competition. The entomopathogenic nematodes isolated in this study were classified as Heterorhabditis kankabi n. sp., and Metarhabditis rainai through light and electronic microscopy, sequencing of ITS and 28S ribosomal DNA regions, and phylogenetic analyses. The bacteriophage nematode M. rainai was recognized as a facultative necromenic nematode, as it consumed the food resources obtained by entomopathogenic nematodes, directly affecting the life cycle of the later by stopping their development and forcing them to leave G. mellonella in search of new hosts.